Optimization on the number of open security lanes at Keflavik International Airport - Sandra Ósk Magnúsdóttir 1992- (2019)
Growing numbers in air transport passengers and increased emphasis on security have created pressure for airports to make changes in their operations to optimize their financial structure without deviating from increased security standards. The air traffic through Iceland has increased along with the global air transport expansion and has created a variety of problems for Isavia regarding the flow of passenger through Keflavik International Airport, which is the main airport in Iceland. One of the emerging problems is to minimize the cost of operating the security lanes while maintaining customer satisfaction by constraining waiting time at the security checkout. The problem has been solved before with different approaches, e.g. queuing theory and simulation, where the main focus is on the security process. An optimization model is presented in this work to decide the number of open security lanes to fit the service level goal Isavia has set to follow. The model is tested on historical data in order to analyze how well the model reflects reality and compare the quality of the optimal solution with the actual configuration by testing the model one morning at the airport. Vaxandi farþega fjöldi og aukin áhersla á flugöryggi hefur skapað þrýsting fyrir flugvelli til að gera breytingar á rekstri sínum til að hámarka fjárhagslega uppbyggingu sína án þess að víkja frá öryggisstöðlum. Flugumferð um Ísland hefur aukist í takt við alþjóðlega aukningu og hefur skapað fjölda vandamála fyrir Isavia varðandi flæði farþega um Keflavíkurflugvöll, sem er aðalflugvöllur Íslands. Eitt af vandamálunum sem hafa myndast, er að draga úr kostnaði við rekstur vopnaleitavéla samhliða því að viðhalda ánægju viðskiptavina með því að takmarka bið þeirra í vopnaleitinni. Vandamál þetta hefur verið leyst áður með mismunandi aðferðum, t.d. biðraðafræði og hermun þar sem aðaláherslan er á öryggisferlið sjálft. Bestunar líkan er kynnt til að ákveða fjölda opinna vopnaleitavéla með það í huga að fara eftir þeim þjónustustöðlum sem Isavia hefur ...